Expanding the Scope of Immunotherapy in Colorectal Cancer: Current Clinical Approaches and Future Directions. (27th January 2020) - Kreidieh, Malek; Mukherji, Deborah; Temraz, Sally; Shamseddine, Ali
Abstract : The success of immune checkpoint inhibitors (ICIs) in an increasing range of heavily mutated tumor types such as melanoma has culminated in their exploration in different subsets of patients with metastatic colorectal cancer (mCRC). As a result of their dramatic and durable response rates in patients with chemorefractory, mismatch repair-deficient-microsatellite instability-high (dMMR-MSI-H) mCRC, ICIs have become potential alternatives to classical systemic therapies. The anti-programmed death-1 (PD-1) agents, Pembrolizumab and Nivolumab, have been granted FDA approval for this subset of patients. Unfortunately, however, not all CRC cases with the dMMR-MSI-H phenotype respond well to ICIs, and ongoing studies are currently exploring biomarkers that can predict good response to them. Another challenge lies in developing novel treatment strategies for the subset of patients with the mismatch repair-proficient-microsatellite instability-low (pMMR-MSI-L) phenotype that comprises 95% of all mCRC cases in whom treatment with currently approved ICIs has been largely unsuccessful. Approaches aiming at overcoming the resistance of tumors in this subset of patients are being developed including combining different checkpoint inhibitors with either chemotherapy, anti-angiogenic agents, cancer vaccines, adoptive cell transfer (ACT), or bispecific T-cell (BTC) antibodies. This review describes the rationale behind using immunotherapeutics in CRC. It sheds light on the progress made in the use of immunotherapy in the treatment of patients with dMMR-MSI-H CRC. It also discusses emerging approaches and proposes potential strategies for targeting the immune microenvironment in patients with pMMR-MSI-L CRC tumors in an attempt to complement immune checkpoint inhibition.